PENERAPAN AL-ASHLU BAQA’U MA KANA PADA TRANSAKSI UTANG PIUTANG - Alfina, Feby (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The principle of Al-Ashlu Bāqa'u Mā Kāna 'Alā Mā Kāna, which means "the law as long as something remains as before," is one of the fiqh rules used in various aspects of muamalah, including debt and receivable transactions. This principle implies that the original state of an object or transaction is considered fixed until there is evidence that changes it. This article aims to examine the application of the principle of Al-Ashlu Bāqa'u Mā Kāna 'Alā Mā Kāna in debt and receivable transactions in the context of Islamic law. This research uses a qualitative method with a literature study approach, exploring relevant primary and secondary sources..